The development and efficacy of an interdisciplinary chronic pelvic pain program - Katz, Laura; Fransson, Adria; Patterson, Lisa (Canadian Urological Association Journal, 2020)
Introduction: Chronic pelvic pain (CPP) is a significant issue, and approximately 14% of women experience CPP once in their lifetime. While interdisciplinary pain management is considered the gold standard of treatment, few programs offer this type of treatment in Canada. The aims of this paper were to: 1) describe the development of an interdisciplinary CPP program; and 2) demonstrate changes in patient-related outcomes after attending an interdisciplinary CPP program. Methods: Referrals were received from community urologists and obstetricians/gynecologists, and pain physicians at the Michael G. DeGroote Pain Clinic. Patients attended an orientation session, completed an interdisciplinary assessment, and if appropriate, attended an eight-day interdisciplinary CPP program. Each day consisted of group-based pelvic floor physiotherapy, psychoeducation, goal-setting, cognitive behavioral therapy, and mindfulness. Psychometric questionnaires were completed pre- and post-program by patients, and paired sample t-tests were used to evaluate the changes in patient-related outcomes after attending the program. Results: Thirty-seven female patients completed the program, and results demonstrate that the CPP program was associated with significant improvements in impact of pelvic pain on quality of life, readiness for change, and pain-related self-efficacy, as well as decreases in pain catastrophizing and fear of pain/re-injury. Conclusions: CPP is a complex condition that requires interdisciplinary management and care. The results of this study demonstrate the short-term benefits of an interdisciplinary CPP program, highlight the unique needs of women with CPP, and implicate multiple factors for programming and treatment.